Establishment of the correlation between the near-surface sedimentary thickness and the microtremor dominant frequency in the Hanoi area - Nguyen-Tien, Hung; Nguyen-Hong, Phuong; Nguyen-Le, Minh; Che-Min, Lin; Tran-An, Nguyen; Pham-The, Truyen; Nguyen-Van, Duong (Vietnam Journal of Earth Sciences, 2022)
This paper established the correlation between the near-surface sedimentary thickness (D) and the microtremor dominant frequency (F0) in the Hanoi area based on 64 microtremor measuring points at the boreholes with depth to bedrock. The microtremor dominant frequency was determined using the horizontal-to-vertical (H/V) spectral ratio of the seismic noise technique proposed by Nakamura (1989). The near-surface sedimentary thickness was determined according to the borehole data from the previously published reports. The non-linear regression method was applied to the pairs of D and F0 values from 64 boreholes to obtain the relationship of form D = 81.851*F0-0.942. This correlation function was used to determine the values of the near-surface sedimentary thickness at microtremor measurement points according to the F0 values. Comparison of the D-values obtained in this study with those from the boreholes data shows good coincidence by values and variation tendency, especially in areas with shallow cover thickness from 50 to 100 m. The above results allow the proposal of a new near-surface sedimentary thickness determination technique in the Hanoi area.